(untitled) (Książnica Śląska, 2025)
The article describes the Polish first performance of Bruno Jasieński’s play The Mannequins’ Ball (20th July 1957), which was one of the most important performances of the Silesian Theater in Katowice under the direction of Józef Wyszomirski, and the diploma work and debut of the outstanding playwright Jerzy Jarocki. The author presents the history of the work’s creation, the history of the Polish first performance and places it in the socio-political life of Poland and the Katowice Voivodeship at that time. The voices of the critics illustrate the extraordinary and unexpected social resonance of this important performance in the history of the Silesian Theater.